The Role of the Posterior Parietal Cortex in the Planning of Saccadic Eye Movements - Ryan, Suzanne (2007)
This thesis aimed to investigate the role of posterior parietal cortex (PPC) in relation to saccade planning and more specifically the spatial remapping processes essential to this behaviour. These experiments begin through the use of transcranial magnetic stimulation (TMS) on a version of the classic double-step saccade paradigm (Chapter 2). TMS was not found to disrupt spatial remapping on this task and a potential explanation for this in terms of task specifications was proposed. In Chapter 4 this theme was explored further through a series of variations on the double-step saccade task, in which the order of target presentation was manipulated; these led to the conclusion that both target encoding and spatial remapping are influenced by such task-related factors. In Chapter 3, a second set of TMS experiments is discussed, which investigated the updating of saccade plans in response to a change in target location, rather than eye position. Finally in Chapters 5 and 6 neuroimaging studies that aimed to evaluate the cortical areas involved in these processes are discussed. The first of these (Chapter 5) was an extension of the behavioural studies previously conducted in Chapter 4. The second employed a novel saccade paradigm to investigate the effect of intervening saccades made between the time of target encoding and execution (Chapter 6). The findings from these experiments supported the idea that the PPC is important for representing saccade goals and updating these following a change in the spatial relationship between the centre of gaze and the target location for a future saccade. In Chapter 7 the findings from the aforementioned studies were discussed in relation to current debate within this area of research, concerning in particular the functional significance of saccade-related neuronal activity in PPC, as were suggestions for future studies that might help provide further insight into these issues.